2018
DOI: 10.1016/j.pbb.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide attenuates cocaine-induced behavioral sensitization and conditioned place preference in mice

Abstract: Cocaine addiction is a chronically relapsing disorder characterized by compulsive drug-seeking and drug-taking behaviors. Previous studies have demonstrated that cocaine, as well as other drugs of abuse, alters the levels of lipid-based signaling molecules, such as N-acylethanolamines (NAEs). Moreover, brain levels of NAEs have shown sensitivity to cocaine self-administration and extinction training in rodents. Given this background, the aim of this study was to investigate the effects of repeated or acute adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Decreased levels of OEA and PEA in nucleus accumbens after the cocaine challenge only in rats self-administering cocaine suggest an impaired control of the release of neurotransmitters during reinstatement, and correlate with the previously reported the participation of the TRPV1 receptor [13,20,28]. Recently, Zambrana-Infantes et al (2018) demonstrated that repeated administration of PEA can block behavioral cocaine sensitization in the mechanism, probably independent of the PPAR-α receptor, but rather as a result of the anti-inflammatory properties of PEA [29]. The decrease in PEA and OEA in the nucleus accumbens observed in our study may confirm the increased cocaine sensitization as a result of the habit forming, since the same changes have not been observed in cocaine-experienced animals following repeated passive (yoked) treatment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Decreased levels of OEA and PEA in nucleus accumbens after the cocaine challenge only in rats self-administering cocaine suggest an impaired control of the release of neurotransmitters during reinstatement, and correlate with the previously reported the participation of the TRPV1 receptor [13,20,28]. Recently, Zambrana-Infantes et al (2018) demonstrated that repeated administration of PEA can block behavioral cocaine sensitization in the mechanism, probably independent of the PPAR-α receptor, but rather as a result of the anti-inflammatory properties of PEA [29]. The decrease in PEA and OEA in the nucleus accumbens observed in our study may confirm the increased cocaine sensitization as a result of the habit forming, since the same changes have not been observed in cocaine-experienced animals following repeated passive (yoked) treatment.…”
Section: Discussionsupporting
confidence: 79%
“…They act through the nuclear proliferator-activated receptor alpha (PPARα), the transient receptor potential vanilloid 1 (TRPV1), and the orphan G-protein-coupled receptors GPR55 and GPR119. NAEs participate in the regulation of many physiological processes and they have neuroprotective, antinociceptive, and anti-inflammatory effects [29]. In this paper, we found that a cocaine-induced relapse resulted in a potent increase in OEA levels in the prefrontal cortex and striatum and in PEA in the prefrontal cortex, hippocampus and dorsal striatum.…”
Section: Discussionmentioning
confidence: 63%
“…83 Palmitoylethanolamide blocks cocaine behaviors in animals as measured by conditioned place preference. 84 GPR55 is highly expressed in the gastrointestinal tract and modulates inflammatory responses. 85 Palmitoylethanolamide has the potential to influence intestinal motility, secretion, inflammation, and cellular proliferation, not only through GPR55 but also by way of PPAR-a and the entourage effect on CB1 and CB2.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…More methodological details and results from these groups are shown in the Supplementary Material Information. All the experiments were conducted during the light phase of the light/dark cycle following previous standardised and published protocols from our group (Castilla-Ortega et al, 2016; Ladrón de Guevara-Miranda et al, 2018; Zambrana-Infantes et al, 2018).…”
Section: Methodsmentioning
confidence: 99%